Coronary Atherosclerosis and Aortic Valve Disease as Long-Term Sequelae of Radiation Therapy in Childhood - Majken van den Handel Vestergaard; Ann Bovin; Erik Lerkevang Grove (Case Reports in Cardiology)
Coronary atherosclerosis and valvular heart disease are rare, but potentially severe sequelae following mediastinal radiation therapy. We present a case of premature ischemic heart disease and severe aortic stenosis in a 40-year-old woman following radiation therapy in childhood. We stress the awareness of prior mediastinal radiation therapy as an important risk factor for premature coronary atherosclerosis and valvular heart disease, particularly in younger patients without classical risk factors for coronary artery disease.